A Hybrid Control Chart-Taguchi Method for Control and Optimization of Safety Conformity - Martins, S.A.; Oke, S.A. (International Journal of Industrial Engineering and Engineering Management, 2020)
In this paper, a hybrid control chart-Taguchi method (CCTM) is proposed to solve the control and optimization problem regarding safety conformity parameters for a bottling process plant (BPP). The CCTM fuses the conservative control charts, which monitor the safety conformity parameters to promote and maintain the uppermost grade of employees’ physical, social and mental well-being. The control chart result is placed in the Taguchi methodical phase of factor-level determination to cultivate an orthogonal array. Then, the inventive rational ability of the control chart is used to correct the process and hence, enhances the Taguchi method. Consequently, the CCTM can be intensely robust and statistically precise. The proposed CCTM was successfully used to solve the safety conformity problem involving the control and parametric optimization in a bottling process plant. The field data uncovers the ability of the proposed CCTM to control and optimize the bottling process plant parameters. Moreover, it showcases the results as better than an enormously stronger than the conventional Taguchi method.